PERILAKU OPORTUNISTIK LEGISLATIF DALAM PENGANGGARAN DAN PENGALOKASIAN DANA DIKABUPATEN MALANG - Abdul Jihad; Abdul Wahid Mahsuni; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
AbstractThis study aims to determine the influence of legislative opportunisticbehavior in budgeting and allocation of funds in Malang. The population in thisstudy is the Malang Regency APBD from 2015 - 2017.The sample in this study is that all populations are used as samples withsaturated sample methods. Analysis is done using simple regression. The resultsof this study indicate that partially legislative opportunistic behavior is notsignificant to budgeting (sig. 0.729), and partially legislative opportunisticbehavior has a significant effect on the allocation of funds (sig. 0.057).Keywords: Budgeting of funds, Allocation of funds and OpportunisticBehavior Legislative